Government digital : the quest to regain public trust - Benay, Alex (Dundurn, 2018)
"Governments worldwide have lost the trust and faith of citizens and other stakeholders. A steady decline in public sector performance, a reluctance to revisit existing business models within government, and the sheer pace of technological change experienced in the past decade have put the public sector at a crossroads. If governments wish to govern stakeholders in ways that reflect their commitment to service, they will need to make a radical change over the next decade. Through the eyes of industry, academic, and government experts, Government Digital lays down a blueprint for that change. Keeping government relevant will take nothing short of a metamorphosis of the public sector. The old ways of doing things cannot continue in the new world, or governments worldwide risk becoming obsolete."--